ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PERMINTAAN DAGING AYAM BROILER OLEH RUMAH TANGGA DI KELURAHAN SEMOLOWARU (STUDI KASUS PASAR SEMOLOWARU) - Zulhazmi, Muhammad Fikri; wiwoho, Bambang (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
Broiler chicken is one type of broiler that has high productivity, especially in producing chicken meat. According to economics, demand is the various types and quantities of goods and services demanded by buyers at various possible prices in a given period in the market. The writing design used in this study uses 1 dependent variable, namely demand and 7 independent variables, namely the price of boiler chicken meat, the price of chicken meat, the price of duck meat, the price of beef and the price of mutton, the number of families and income. The type of data used in this study uses primary data. Data was collected through questionnaires filled out by households while conducting research at Semolowaru Market, Surabaya. The sample in the study was 100. The data were analyzed using multiple linear regression statistical tests. The results of the t-test analysis showed that only the price of boiler chicken meat, the price of native chicken meat had a significant effect on the demand for boiler chicken meat. Meanwhile, the variables of duck meat price, beef price, mutton price, number of families and income have no significant effect on the demand for boiler chicken meat. The F test shows that the seven factors together can be said to affect the demand for boiler chicken meat. The results of the calculation of the elasticity of demand for boiler chicken meat obtained that the elasticity value of boiler chicken meat is 0.370, meaning that boiler chicken meat is inelastic